1966
DOI: 10.1002/cber.19660990116
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclen aus CH‐aciden Nitrilen, VIII. 2‐Amino‐thiophene aus methylenaktiven Nitrilen, Carbonylverbindungen und Schwefel

Abstract: WAliphatische Ketone, Aldehyde sowie P-Dicarbonylverbindungen reagieren mit methylenaktiven Nitrilen und Schwefel in Gegenwart von Aminen bei Raumtemperatur zu 2-Aminothiophenen. -Eine Variante der Synthese, die Einwirkung von Schwefel auf vinyloge methylenaktive Nitrile, gestattet auch die Einbeziehung von Alkylarylketonen in die Reaktion.In der vorangegangenen Mitteilung 1 ) haben wir iiber die Bildung von 2-Aminothiophenen aus a-0x0-mercaptanen und methylenaktiven Nitrilen berichtet (Gl. 3). Wie wir bereits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
348
0
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 783 publications
(358 citation statements)
references
References 12 publications
2
348
0
8
Order By: Relevance
“…The most convergent and well established classical approach for the preparation of 2-aminothiophenes is Gewald's method [2,3], which involves the multicomponent condensation of aketone with an activated nitrile and elemental sulfur in the presence of diethylamine as acatalyst. The crystal structure of 5-acetyl has been reported [4].…”
Section: Discussionmentioning
confidence: 99%
“…The most convergent and well established classical approach for the preparation of 2-aminothiophenes is Gewald's method [2,3], which involves the multicomponent condensation of aketone with an activated nitrile and elemental sulfur in the presence of diethylamine as acatalyst. The crystal structure of 5-acetyl has been reported [4].…”
Section: Discussionmentioning
confidence: 99%
“…The regioselectivity of the ring closure reactions was evident from NOESY and HMBC experiments. In summary, we have shown that fully protected ribofuranosylpropanal (1), 2-deoxyribofuranosylpropanal (14) and the corresponding alkynyl ketones 19, 20, 29, and 30 are suitable intermediates for the preparation of homo-and spacered C-nucleosides. The tetrahydrofuran ring and the protecting group pattern is stable enough even under drastic reaction conditions to allow the synthesis of a broad variety of heterocyclic systems.…”
Section: Synthesis Of Triazolo-and Pyrimidinobenzimidazole-spacered Cmentioning
confidence: 97%
“…alcohols, amines, aldehydes, and acetylenic ketones. 12 In this contribution we present our results on transformation of the furnished aldehydes (1,14) and acetylenic ketones (19,20, 29, 30) as versatile intermediates into a selected number of different heterocycles to make the synthetic potential of these precursors visible.…”
Section: Introductionmentioning
confidence: 99%
“…The biological evaluation of the products was carried out at the Micro Analytical Center in Cairo University, Cairo, Egypt. Compounds 1 [18][19][20][21][22] and 2a [23] were prepared according to known methods (Scheme 1).…”
Section: Instrumentationmentioning
confidence: 99%
“…The diazo coupling reaction of the starting ethyl 2-amino-4-phenylthiophene-3-carboxylate (1) [18][19][20][21][22] with diazotized aromatic and heterocyclic amines resulted in the formation of the corresponding 5-aryl-and 5-heteroarylazo derivatives 2a-d (Scheme 1). Hydrazinolysis of 4-methoxyphenylazo derivative 2b in ethanol provided the target aminocarbohydrazide 3, whose structure was confirmed by examining spectroscopic data and elemental analysis.…”
Section: Chemistrymentioning
confidence: 99%